If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 52 = -37 Reorder the terms: 52 + y = -37 Solving 52 + y = -37 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + y = -37 + -52 Combine like terms: 52 + -52 = 0 0 + y = -37 + -52 y = -37 + -52 Combine like terms: -37 + -52 = -89 y = -89 Simplifying y = -89
| 46=18a | | 12y+58+(-12)=6y+8 | | -20-28n=-10n-2 | | -4+50=a | | 7x-2-6x=5 | | w-11=-8 | | -4-50=a | | -12+3=8-2r | | 101=5a+1 | | -4=-18a-50 | | 12a+4=16 | | 4+(34)=3x+0 | | 12y+30=6t | | 5-2x=5-7x+5x | | 5(h+1)=25 | | 3a+4=2x-1 | | 7(6x-8)-5x= | | -3x-x=-24 | | 6(x+2)=5x+4-2x | | 4+(34)=3 | | z/5-6=1,1/8 | | 3(x-7)(2x-4)=0 | | 6.7(x-1)=-0.3x+42.3 | | 1/7+d=1/2/7 | | 0=60t-5t^2 | | z/5-6=1/8 | | 11s-12=10 | | 2x-5+4x=6(x+2) | | 5-(4x-2)+16x=108 | | 1.5x+4.4=11.9 | | h=60t-5t^2 | | 38c=-26 |